WACANA PEMBEBASAN PEREMPUAN; Studi Kritis Pemikiran Qasim Amin dan Jamal al-Banna - Syaiful Bahri (LP2M Universitas Ibrahimy, 2014)
Women's liberation movement (feminism) rose up when the practice of marginalization and subordination occurs. They were Qasim Amin and Jamal al-Banna, the two Muslim feminist from different generations, who tried to decipher the discourse of liberation against women. This paper concerns to discuss the idea of the two figures. To analyze this problem, the authors conducted a literature study to assess the work of both of which relate to the problems of women, Tahrir al-Mar‘ah by Qasim Amin and Al-Mar‘ah al-Muslimah bayna Tahrir Al-Qur’an wa Taqyid al-Fuqaha’ by Jamal al-Banna. These studies lead to the conclusion that the discourse of women's liberation initiated by Amin and Jamal cannot be separated from the paradigm of feminism owned by each figure. Both Amin and Jamal stated that the practice of marginalization and subordination of women is not from the nature of religion, but it was from the culture and misunderstanding on religious teachings.